Ambidestria e sua relação com o desempenho organizacional - Miranda, Laura Melo Barros Bona (2015)
This thesis involves the study of the relationship between organizational performance and guidelines for exploration, exploitation and ambidexterity. For the development of this study, two concepts were objects of theoretical considerations and empirical evaluations. The first consists of the types of guidelines used by organizations in the acquisition, organization and management of knowledge, termed as exploration, exploitation and ambidexterity. The second concept refers to organizational performance, this research is based on the Balanced Scorecard - BSC. This study focused on these two concepts can be justified by the importance and influence of the management of organizational knowledge in generating superior performance compared with other companies in the same sector or industry. Besides presenting a theoretical review of the related literature to the issues in question, this study also replicated two scales, a performance measurement proposed by Popadiuk (2006) is divided into four indicators that measure the financial performance indicators that measure 10 customer management, 10 internal management processes and eight that measure learning and growth and other measurement of ambidexterity, exploration and exploitation which consists of 45 indicators, 20 of which classify the company as exploitative and 25 which together rank the company as explotadora. The sample included 249 respondents and the data were processed and validated by means of the technique of Structural Equation Modeling with estimation method Partial Least Squares (PLS) using the SmartPLS 2.0 software. The results were validated empirically. One can also conclude that for this sample the sector of the economy, did not constitute a moderating variable of the relationship between ambidexterity and organizational performance.